2007
DOI: 10.1002/ajmg.b.30490
|View full text |Cite
|
Sign up to set email alerts
|

MECP2 coding sequence and 3′UTR variation in 172 unrelated autistic patients

Abstract: Mutations in the coding sequence of the methyl‐CpG‐binding protein 2 gene (MECP2), which cause Rett syndrome (RTT), have been found in male and female autistic subjects without, however, a causal relation having unequivocally been established. In this study, the MECP2 gene was scanned in a Portuguese autistic population, hypothesizing that the phenotypic spectrum of mutations extends beyond the traditional diagnosis of RTT and X‐linked mental retardation, leading to a non‐lethal phenotype in male autistic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…More recent studies have identified mutations in MECP2 regulatory regions in autistic boys (13,34), rather than protein coding mutations found in female Rett syndrome patients. These results may be explained on the basis of the extra (inactive) copy of the X chromosome providing redundancy or buffering to severe protein-coding mutations in females.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have identified mutations in MECP2 regulatory regions in autistic boys (13,34), rather than protein coding mutations found in female Rett syndrome patients. These results may be explained on the basis of the extra (inactive) copy of the X chromosome providing redundancy or buffering to severe protein-coding mutations in females.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in control and autistic patients suggest that there are numerous variations in 3′UTR between them, and these transcripts have different translational efficiencies. Some of these transcript variants are more unstable and undergo transcriptional degradation (Coutinho et al 2007). Newnham et al, reported the presence of cis-acting elements which can regulate the polyadenylation of human MECP2 gene and mutations of which can reduce the polyadenylation efficiency.…”
Section: Polyadenylationmentioning
confidence: 99%
“…Reduced MECP2 expression in autistic patients has been associated with increased MECP2 promoter DNA methylation (Nagarajan et al 2006(Nagarajan et al , 2008. Moreover, MECP2 mutations within the coding regions (Carney et al 2003;Beyer et al 2002;Lam et al 2000;Loat et al 2008) and sequence variants within the MECP2 3′UTR (Shibayama et al 2004;Coutinho et al 2007) are also found in autistic patients, indicating the potential involvement of these sequence variations in altered expression of MECP2 in autism. Not only reduced MECP2 expression, but also overexpression of MECP2 is found in ASD patients (Kuwano et al 2011).…”
Section: Mecp2 and Other Human Diseases Autism Spectrum Disordersmentioning
confidence: 99%
“…Their relative rarity may be in part because not all regulatory elements occur immediately 5 0 to the genes that they regulate. Indeed, many such elements are located within the first exon, within introns [Cecchini et al, 2009] or within 5 0 or 3 0 untranslated regions (UTRs); regulatory elements within intronic sequences and UTRs are less likely to be screened for mutations [Chatterjee and Pal, 2009;Chen et al, 2006a,b], particularly if the UTRs are large (e.g., MECP2; MIM] 300005) [Coutinho et al, 2007]. Recently, a whole new category of pathological mutation has been recognized within the 3 0 UTRs of human genes: genetic variants located in microRNA target sites either causing, or associated with an increased risk of, inherited disease [Bandiera et al, 2010;Martin et al, 2007;Rademakers et al, 2008;Sethupathy and Collins, 2008;Simon et al, 2010].…”
Section: Mutations Residing Within Proximal Gene Regulatory Regionsmentioning
confidence: 99%